Key audit matters versus financial indicators: consistent or contradictory? - Lee, Wei Min; Phua, Lian Kee (2018)
The ISA 700 (Revised) Forming an Opinion and Reporting on Financial Statements has mandated the independent auditors to communicate key audit matters of the audited financial statements to enhance the value of the auditor’s reports. This study aims to examine whether the key audit matters identified by the independent auditors are in line with the financial performance indicators derived from the financial information provided in the financial statements. The study uses secondary data obtained from the independent auditor’s report and Datastream database. The key audit matters tested in this study are revenue recognition, trade receivable, and inventory issues which are found to be frequently reported in the independent auditor’s report. The key audit matters are categorized into groups. T-test is done to analyse the difference in mean of financial ratios between the group that was identified to have key audit matter and otherwise. The result shows significant difference in mean of certain financial ratios between the groups. We found that the key audit matter disclosed is in line with the financial performance indicators. This is supported by the evidence that those firms identified to have trade receivable issue as key audit matter by the independent auditor also show poor performance on average collection period and total asset turnover. On the other hand, the key audit matter related to significant judgements by the auditors in areas of higher assessed risk of material misstatement did not reflect on financial performance indicators. The firms that suffered from revenue recognition and inventory issues performed better according to the financial ratio. The findings of this study provide evidence that the identified key audit matter need to be interpreted according to the nature of issues as there are mixed relationship observed between key audit matters and financial indicators.